Irreversible electroporation of multiple blood cells in continuous flow microfluidic device-A theoretical study - Basha, I.H.K. (Institute of Electrical and Electronics Engineers Inc., 2017)
In this paper, we present a theoretical study on irreversible electroporation of multiple blood cells in a continuous flow microfluidic device for high throughput applications. Irreversible electroporation is the cell lysis process in which the application of electric field permanently permeabilizes the cell membrane, allowing the intercellular content to eject out for downstream genetic analysis. The device geometry can be manipulated for fluid transport and irreversible electroporation. Our study concentrates on the effect of voltage, flow velocity, geometry and the location of cells inside the device for efficient irreversible electroporation. Our results show that by controlling the applied voltage, cells can be irreversibly electroporated. The flow velocity influences irreversible electroporation. If the flow velocity is greater than the resident velocity of the cell, the pores on the membrane will reseal thereby resulting in reversible electroporation. The nanofluidic channels increase the duration of electroporation as the larger cells cannot pass through them. © 2016 IEEE.